1986
DOI: 10.1172/jci112665
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of glucagon and triiodothyronine on the hepatic levels of messenger ribonucleic acid S14 and the dependence of such effects on circadian factors.

Abstract: We have studied the effect of glucagon on the expression of a triiodothyronine (T3) and carbohydrate-inducible mRNA sequence (mRNA-S14) in rat liver that undergoes a threefold diurnal variation (peak, 2200 h; nadir, 0800 h). Glucagon injection into euthyroid rats (25 ig/100 g body wt i.p., three doses at 15-min intervals) during the nocturnal plateau of mRNA-S14 caused a monoexponential disappearance of this sequence (t1/2, 90 min) accompanied by a 90% reduction in the transcriptional rate in a nuclear run-off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In the present experiments, how¬ ever, in which a wide dose range of T3 was adminis¬ tered, marked stimulatory actions of T3 were achieved only at 72 h after daily T3 replacement was commenced; furthermore, a clear dose-de¬ pendent effect was evident at this time point. Stimulatory actions of T3 treatment in the euthy¬ roid state were also demonstrated in the present studies, in accord with a report of a 2-fold increase in Spot 14 mRNA 1.5 h after injection of T:i (200 (ig) in the euthyoid rat (17). In contrast to the absence of a sustained effect of T3 treatment of the hypothy¬ roid rat at 6 h, a dose-dependent stimulation of Spot 14 mRNA was induced in the euthyroid rat at this time point.…”
Section: Discussionsupporting
confidence: 93%
“…In the present experiments, how¬ ever, in which a wide dose range of T3 was adminis¬ tered, marked stimulatory actions of T3 were achieved only at 72 h after daily T3 replacement was commenced; furthermore, a clear dose-de¬ pendent effect was evident at this time point. Stimulatory actions of T3 treatment in the euthy¬ roid state were also demonstrated in the present studies, in accord with a report of a 2-fold increase in Spot 14 mRNA 1.5 h after injection of T:i (200 (ig) in the euthyoid rat (17). In contrast to the absence of a sustained effect of T3 treatment of the hypothy¬ roid rat at 6 h, a dose-dependent stimulation of Spot 14 mRNA was induced in the euthyroid rat at this time point.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, activation of PKA inhibited glucose-induced expression of the S14 (27) and L-PK (28) genes, although for the former, it has been attributed to an effect on glucose metabolism (9) and for the latter to an effect on glucokinase activity. Indeed, the cAMP inhibitory effect on L-PK gene expression was lost in a hepatoma cell line expressing hexokinase II rather than glucokinase (29).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the level of Thrsp mRNA in white adipose tissue, brown adipose tissue, and liver is elevated when de novo fatty acid synthesis is induced by dietary and hormonal stimuli (Freake and Oppenheimer, 1987, Jump et al, 1984, Jump and Oppenheimer, 1985, Kinlaw et al, 1986, Narayan et al, 1984, Towle and Mariash, 1986). To study the role of the Thrsp protein in de novo lipogenesis, we created a Thrsp null mouse and found that the rate of hepatic lipogenesis was normal but mammary gland lipogenesis was markedly reduced (Zhu et al, 2001, Zhu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%